Pemanfaatan Limbah Fly Ash Batubara Untuk Pembuatan Paving Block Geopolimer Dengan Variasi Konsentrasi NaOH Dan Rasio Natrium Silika Terhadap Natrium Hidroksida (Na2SiO3/NaOH) - Wyda N Saragi; Ahmad Fadli; Drastinawati Drastinawati (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
Paving block geopolymer is a material synthesized through a polymerization process which can be used in the construction, especially of homes, buildings and roads. The objective of this research are to determine the effect of the concentration of NaOH and sodium silica to sodium hydroxide ratio (Na2SiO3 / NaOH) and characterization of geopolymer paving blocks made from coal ash. Paving block geopolymer prepared by mixing coal ash and fine aggregate and then added liquid activator (sodium hydroxide and sodium silica). Paving block pour into cube mould with size 5x5x5 cm3. Subsequently the mixture put at room temperature for 24 hours and then dried at curing temperature of 90 ° C for 24 hours. Characteristic of geopolymer paving blocks ie compressive strength, density, porosity, morphology and TCLP test were determined. The compressive strength of paving block geopolymer increase with concentration NaOH and sodium silica to sodium hydroxide ratio. The obtained of compressive strength of paving block geopolymer of 13,730 MPa at concentration NaOH 10M and increase to 19,068 Mpa at concentration NaOH 14 M. The highest density of paving block geopolymer is 2,17 gr/cm3 at concentration NaOH 14 M.Key words : fly ash, geopolymer paving block, sodium hydroxide, sodium silicate